A Library Locker Security System with Integrated RFID, Dual Camera Monitoring, and Telegram Notification - Mario Fazero Siregar; Jufrizel; Ahmad Faizal; Hilman Zarory (Jurnal Sistem Cerdas, 2024)
Abstract- Libraries generally provide lockers for users to store their luggage. Lockers in general still use conventional security by using manual locks. Currently, UIN Suska Riau Central Library still uses conventional key security which is considered easy to duplicate, lose, and damage. The purpose of this research is to improve locker security for user convenience and security through a system integrated with RFID, dual camera monitoring, and telegram notification. This tool has a CRUD (Create, Read, Update, Delete) system embedded in the telegram application managed by the admin. Admin can register, delete, and monitor locker user activities. This tool can identify registered and unregistered RFID tags properly. When a registered user accesses the locker, the system will send a picture of the user and a message to the telegram. Meanwhile, when an unregistered user accesses the locker 3 times incorrectly, the device will send the user's picture and message to the telegram and an alarm will sound for 3 seconds as an indication of an attempted locker break-in. The speed of information notification from the Internet of Things system has a delay in sending images with stability in the range of 3 - 4 seconds with relatively strong internet provider speed stability. Keywords— locker security, internet of things, RFID, dual camera monitoring, telegram